Solving for y
April did u switch your answer? The first time I saw y=8 that's why I corrected it.
Solving for y
April did u switch your answer? The first time I saw y=8 that's why I corrected it.
Basically, you would want to get the "y" term by itself. Below is the step-by-step solution to this process.
Original equation: 3y + 6x = 24
Subtract 6x from both sides to get "3y" by itself: 3y + 6x = 24
- 6x - 6x
New equation: 3y = - 6x + 24
To get "y" by itself, divide each term by 3: 3y = -6x + 24
3 3 3
New equation: y = -2x + 8 <--- THIS IS THE ANSWER
Hope this helps :)
The answer is y=-2x+8 not y=8. you cannot get rid of x.
Yeah...I don't know where you saw the y=8.
Comments
No Lisa. I didn't change it.
I answered this question on the 24th of January and I haven't looked at it since.